2020
DOI: 10.21203/rs.3.rs-23441/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of scrubber discharge on the water quality in estuaries and ports

Abstract: Background: The International Maritime Organization (IMO) has set limits on sulphur content in fuels for marine transport. However, vessels continue to use these residual high sulphur fuels in combination with exhaust gas cleaning systems (EGCS or scrubbers). Next to high sulphur, combustion of these fuels also results in higher emissions of contaminants including metals and PAHs. In scrubbers, exhaust gases are sprayed with water in order to remove SOx, resulting in acidic washwater with elevated contaminant … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Comparing to a list published by Teuchies and colleagues, our closed-loop EGSEs seem to contain PAHs at concentrations several times higher than the average ship, whereas heavy metal concentrations are slightly lower (except for Hg). 43 In our open-loop EGSE, PAH concentrations are close to the average, whereas metal concentrations seems lower than average, except Hg which was five times higher than average. 43 …”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Comparing to a list published by Teuchies and colleagues, our closed-loop EGSEs seem to contain PAHs at concentrations several times higher than the average ship, whereas heavy metal concentrations are slightly lower (except for Hg). 43 In our open-loop EGSE, PAH concentrations are close to the average, whereas metal concentrations seems lower than average, except Hg which was five times higher than average. 43 …”
Section: Resultssupporting
confidence: 54%
“… 43 In our open-loop EGSE, PAH concentrations are close to the average, whereas metal concentrations seems lower than average, except Hg which was five times higher than average. 43 …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Despite the fact that the scrubber water has been used to wash the gases of combusted HFO (pyrogenic origin), there are several characteristics in the PAC ingerprint more resembling a petrogenic than a pyrogenic pro ile. This might be caused by an incomplete combustion of the HFO and/or the presence of oil from other oil sources, e.g., lubrication oil, in the scrubber water (Teuchies et al 2020).…”
Section: Pac Ingerprintmentioning
confidence: 99%
“…Recently several studies have raised concerns about a negative impact on the marine environment where authors pointed out how these guidelines look inappropriate and claimed for stricter regulations to control, in particular, for the emissions of persistent pollutants as PAH and heavy metals from seawater scrubbers (Turner et al 2017(Turner et al , 2018Ytreberg et al 2019;Dulière et al 2020). Teuchies et al (Teuchies et al 2020) showed that scrubber washwater emissions should be discouraged in areas with high levels of pollutions since the amount of emitted pollutants sum to the already polluted background. This conclusion holds true, however, for all the existing sources of pollutants active in that area.…”
Section: Introductionmentioning
confidence: 99%